Perda de eletrólitos radiculares em mudas de Peltophorum dubium e Enterolobium contortisiliquum submetidas a diferentes frequências de irrigação durante a rustificação - Oro, Priscilla (2012)
The search for alternative tests that aim to characterize the physiological quality of seedlings are important and needed. The objective of this work was to evaluate the use and consistency of root electrolyte leakage test in the physiological characterization and survival of Enterolobium contortisiliquum and Peltophorum dubium seedlings submitted to irrigation frequencies during hardening. Seedlings were submitted to six irrigation frequencies for a period of 30 days, when we evaluated increments in height and stem diameter, ratio of height to stem diameter, increments in dry biomass of root, stem and leaves, the ratio of shoot to root dry biomass, total dry biomass, Dickson quality index, and root electrolyte leakage. Seedlings were transplanted to pots with sand and water restriction for 60 days to evaluate survival percentage according to a randomized design. Results showed a negative correlation between electrolyte leakage and survival percentage after 30 and 45 days of water restriction of -0,60 and -0,76 for E. contortisiliquum and -0,70 and -0,75 for P. dubium seedlings, respectively. Root electrolyte leakage showed to be consistent to evaluate physiological quality and survival of Enterolobium contortisiliquum and Peltophorum dubium seedlings subjected to different irrigation frequencies during hardening